Dystocia due to fetal ascites in an ewe - GANDOTRA, V K; GHUMAN, S P S; HONPARKHE, M; KUMAR, AJEET (The Indian Journal of Animal Reproduction, 2003)
A rare case of dystocia due to fetal ascites in sheep and its treatment by caesarian section has beendescribed.
Keywords: Dystocia; fetal ascites